Multi-objective optimal dispatch of microgrid under uncertainties via interval optimization - Li, Yuanzheng (2020)
This paper presents a model of multi-objective optimal dispatch of microgrid (MODMG) under uncertainties via the interval optimization (IO) approach. In this model, multiple objectives are optimized simultaneously to meet economics, power quality, and security requirements of microgrid (MG) operations. Moreover, in order to adequately consider uncertain power outputs of wind turbines and photovoltaic cells in an MG, they are presented as interval variables. In turn, the MODMG model under uncertainties is formulated as a multi-objective optimization problem via the IO approach, which is then solved by the optimization algorithm of chaotic group search optimizer with multiple producers (CGSOMP). Simulation studies based on a modified IEEE 112-bus MG verify the effectiveness of the proposed optimal dispatch model and the CGSOMP algorithm.